2022
DOI: 10.3390/ijms232113291
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Water Solubility and Anti-Tumor Activity of Oleanolic Acid through Chemical Structure Modification

Abstract: Cancer has been a major health problem in the world in the past decades. It is urgent to develop new, effective and safe drugs for the treatment of cancer. There are many pentacyclic triterpenoids with positive anti-tumor activity and safety in nature. Oleanolic acid (OA), as one of the pentacyclic triterpenoids, also has broad biological activities including liver protection, anti-inflammatory, hypoglycemic, antiviral and anti-tumor. Therefore, to investigate its anti-tumor activity and mechanism, many OA der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 121 publications
(134 reference statements)
0
1
0
Order By: Relevance
“…[24][25][26] OA possesses many promising pharmacological activities, including hepatoprotective, [27,28] anti-inflammatory, [29,30] antioxidant, [31] and anticancer activities. [24,32] The hepatoprotective effects of OA allow its use in China as an over-the-counter oral drug for liver disorders such as viral hepatitis in humans. [25,[33][34][35] A recent study reported that neonatal intake of OA prevented and attenuated the subsequent development of high fructose diet-induced NAFLD in rats.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] OA possesses many promising pharmacological activities, including hepatoprotective, [27,28] anti-inflammatory, [29,30] antioxidant, [31] and anticancer activities. [24,32] The hepatoprotective effects of OA allow its use in China as an over-the-counter oral drug for liver disorders such as viral hepatitis in humans. [25,[33][34][35] A recent study reported that neonatal intake of OA prevented and attenuated the subsequent development of high fructose diet-induced NAFLD in rats.…”
Section: Introductionmentioning
confidence: 99%